Milnacipran for neuropathic pain in adults - Derry, Sheena (Cochrane Database Syst Rev, 2015)
BACKGROUND: Milnacipran is a serotonin–norepinephrine reuptake inhibitor (SNRI) that is sometimes used to treat chronic neuropathic pain and fibromyalgia. This is an update of an earlier review of milnacipran for neuropathic pain and fibromyalgia in adults originally published in The Cochrane Library Issue 3, 2012. We split that review so that this one looked only at neuropathic pain, and a separate review looks at fibromyalgia. OBJECTIVES: To assess the analgesic efficacy and associated adverse events of milnacipran for chronic neuropathic pain in adults. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, and EMBASE to 23 February 2015, together with reference lists of retrieved papers and reviews. SELECTION CRITERIA: We included randomised, double‐blind studies of eight weeks' duration or longer, comparing milnacipran with placebo or another active treatment in chronic neuropathic pain. DATA COLLECTION AND ANALYSIS: Two review authors independently searched for studies, extracted efficacy and adverse event data, and examined issues of study quality. We did not carry out any analysis. MAIN RESULTS: We included a single study of 40 participants with chronic low back pain with a neuropathic component. It found no difference in pain scores between milnacipran 100 mg to 200 mg daily or placebo after six weeks (very low quality evidence). Adverse event rates were similar between treatments, with too few data to draw conclusions (very low quality evidence). AUTHORS' CONCLUSIONS: There was no evidence to support the use of milnacipran to treat neuropathic pain conditions.